Development and application of geothermally derived silica grout for carbon-neutral soil stabilization - Taichi Terui; Toshiyuki Motohashi; Shigeo Sasahara; Shinya Inazumi (Case Studies in Construction Materials)
The construction industry is a major contributor to global carbon emissions, driving the need for sustainable construction materials that can mitigate environmental impacts. This study introduces a novel carbon-neutral grout, Colloidal Silica Recovered from Geothermal Fluids (CSRGF), developed using silica extracted from geothermal fluids, a byproduct of geothermal energy production. CSRGF grout is specifically designed to enhance soil stabilization in construction projects while minimizing its environmental footprint. The formulation incorporates colloidal silica with specialty water glass, which not only improves mechanical durability, but also significantly reduces CO2 emissions compared to traditional silica-based grouts. To evaluate the performance of the CSRGF grout, extensive testing was conducted on its key properties, including liquefaction resistance, unconfined compressive strength, water sealing capabilities and environmental safety. The results indicate that CSRGF grout exhibits a significant improvement in liquefaction resistance and compressive strength while maintaining low viscosity and controlled gelling times, which are essential for effective soil penetration and stabilization. In addition, the production process of CSRGF grout is consistent with carbon neutrality goals, contributing to a significant reduction in CO2 emissions. This innovative material not only represents an advancement in soil stabilization technology, but also aligns with the broader goal of reducing the carbon footprint of the construction industry, thereby supporting global sustainability initiatives and promoting more sustainable construction practices.